Studi Kemungkinan Pemakaian Sekam dan Jerami Padi sebagai Bahan Bakar Briket untuk Ketel Uap di RSUP dr. Wahidin Sudirohusodo Makassar - David Mangallo; Duma Hasan (Politeknik Negeri Ujung Pandang, 2012)
This study aims to: (1) make briquettes from rice husk and straw with some mixture proportions, (2) determine the heating value (HHV) and the compressive strength of the produced briquettes (3) determine the physical properties of the produced briquettes through the proximate analysis and determine the best briquettes mixture, and (4) know the possibility of using rice husk and straw as briquette fuel for steam boilers. The produced briquettes contained 85% of rice husk charcoal and straw, and adhesive subtance consisting of clay (10%) and strach (5%). The briquettes were made with five mixture proportions with an average mass ratio of 260 gramsduce briquettes briquette type E as the best. The examination of heating value reveals that the higher the percentage of staw in the mixture, the lower the briquette heating value will be; while the testing of compressive strength reveals that the higher the percentage of straw in the mixture, the higher the briquette compressive strength will be. Based on the proximate analysis, it is found that generally the produced briquettes have fulfilled the briquette standard quality. The results of calculations analysis reveal that there is a possibility to use briquettes made of rice husks and straw as steam boilers the ratio between the fuel mass flow rate and vapor mass flow rate is 0.231.